2019
DOI: 10.1021/acsbiomaterials.8b01092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biomedical Applications of Copper Oxide Nanoparticles: An Expanding Horizon

Abstract: Synthesis of copper oxide nanoparticles with tunable size and desirable properties is a foremost thrust area of the biomedical research domain. Though these features primarily rely on the synthetic approaches involved, with advancements in this area, it has been documented that the synthesis parameters and surface modifiers have a direct impact on the morphology and eventually on the biomedical properties. “Sensing” remains a major application of nanomaterials owing to their small size and unusual physicochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(115 citation statements)
references
References 196 publications
(372 reference statements)
0
114
0
1
Order By: Relevance
“…Although clinical application of copper oxide nanoparticles is controversial due to potential adverse effects to human cells, several studies reported less or no toxicity of copper oxide nanoparticles 59,70 . Unfortunately, the dependence of efficient bactericidal activity of Cu 2 O NPs up on the dissolved Cu +1 ions and solubility of www.nature.com/scientificreports/ the nanoparticles at lower pH significantly decreases their potential clinical applications at physiological pHs (6)(7)(8).…”
Section: Dissolution and Cellular Uptake Of Cumentioning
confidence: 99%
“…Although clinical application of copper oxide nanoparticles is controversial due to potential adverse effects to human cells, several studies reported less or no toxicity of copper oxide nanoparticles 59,70 . Unfortunately, the dependence of efficient bactericidal activity of Cu 2 O NPs up on the dissolved Cu +1 ions and solubility of www.nature.com/scientificreports/ the nanoparticles at lower pH significantly decreases their potential clinical applications at physiological pHs (6)(7)(8).…”
Section: Dissolution and Cellular Uptake Of Cumentioning
confidence: 99%
“…Copper oxide (Cu 2 O) is claimed to be a transition metal oxide having narrow bandgap, i.e., ~2.0 eV and shows distinct features like significant electrochemical activity, improved redox potential, high specific surface area and incomparable stability in solutions. It is the second choice of researchers working in the field of nanotechnology after the noble metal nanoparticles, owing to its propitious application in different subjects like antifouling coatings, biocidal agents, catalysis, sensors/biosensors, electrochemistry and energy storage [ 72 ]. These nanoparticles are extensively used for non-enzymatic sensing of clinical analytes due to their ability to promote electron transfer reaction even at low potential [ 72 ].…”
Section: Green Synthesis Of Nanoparticles Mediated By Fruit Extracmentioning
confidence: 99%
“…It is the second choice of researchers working in the field of nanotechnology after the noble metal nanoparticles, owing to its propitious application in different subjects like antifouling coatings, biocidal agents, catalysis, sensors/biosensors, electrochemistry and energy storage [ 72 ]. These nanoparticles are extensively used for non-enzymatic sensing of clinical analytes due to their ability to promote electron transfer reaction even at low potential [ 72 ]. The Cu 2 ONPs derived from fruits have been listed along with various applications in Table 3 .…”
Section: Green Synthesis Of Nanoparticles Mediated By Fruit Extracmentioning
confidence: 99%
“…In particular, nanoparticles of the relatively cheap and abundant copper (CuNPs) have found multiple applications in diverse areas, including catalysis [ 5 ] and materials science [ 6 , 7 ]. However, CuNPs have also been exploited for disinfection purposes because of their effective antimicrobial properties, in medicinal chemistry or as farm animal food additives [ 8 , 9 , 10 ]. Nevertheless, copper nanoparticles can adversely influence various biological processes [ 11 , 12 , 13 ] and produce some toxicological effects on individual organisms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%